2007
DOI: 10.1021/ma071272q
|View full text |Cite
|
Sign up to set email alerts
|

Copolyesters Based on Poly(butylene terephthalate)s Containing Cyclohexyl and Cyclopentyl Ring:  Effect of Molecular Structure on Thermal and Crystallization Behavior

Abstract: In an effort to understand the role of molecular structure on the thermal properties of polyesters and copolyesters, the following polyesters were synthesized:  poly(1,4-cyclohexane dimethylene terephthalate) (PCT), poly(butylene-1,4-cyclohexane dicarboxylate) (PBCD), poly(1,3-cyclopentane dimethylene terephthalate) (PCPDT), and poly(butylene-1,3-cyclopentane dicarboxylate) (PBCP). PCT and PCPDT are semicrystalline polymers with crystallization and melting temperatures higher than poly(butylene terephthalate) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 39 publications
0
38
0
Order By: Relevance
“…T CC a) [4] Therefore, on the basis of all such experimental evidences it may reasonably be inferred that a single crystalline phase is present for all semicrystalline PBCHD samples. Figure 2 shows some typical calorimetric traces of the PBCHD samples that were isothermally crystallized at different temperatures (T C ) and subsequently melted.…”
Section: Samplementioning
confidence: 76%
See 1 more Smart Citation
“…T CC a) [4] Therefore, on the basis of all such experimental evidences it may reasonably be inferred that a single crystalline phase is present for all semicrystalline PBCHD samples. Figure 2 shows some typical calorimetric traces of the PBCHD samples that were isothermally crystallized at different temperatures (T C ) and subsequently melted.…”
Section: Samplementioning
confidence: 76%
“…Consequently, T g raises and desirable physical-mechanical properties can be obtained. [3,4] The comparison between the glass transition temperatures of poly(butylene adipate) (PBA) and poly-(butylene 1,4-cyclohexanedicarboxylate) (PBCHD), whose chemical structure is reported in Scheme 1, can be significant. The T g values are -58 8C for PBA [5] and vary from -10 to 18 8C for PBCHD, [6] i.e., difference of about 50-80 8C.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, research developments in bio-based polyesters with a high biomass content need to consider the fact that maintaining the aromatic polyester properties is crucial to synthesizing versatile materials for engineering plastics. 25 Recently, much research has been carried out and it has been reported that copolyesters based on CHDM monomers have signicant effects. The chain segment has a trans-gauche-gauche-trans conformation (4GT) which, compared to 2GT chain segment monomers, gives rise to outstanding elastic recovery properties when incorporated into an aromatic polyester.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13] The renewable monomer, 1,3-propanediol (PDO), is a representative monomer that succeeded in being commercially produced via the use of biological processes. 11,[25][26][27][28] The copolyester derived from CHDM and terephthalic acid (TPA) has an excellent impact strength due to conformational a, a/e, e transitions, resulting from an increase of the chain mobility. Because of polyamide and polyester characteristics, the main application of aromatic polyesters using PDO is in the carpet industry in the production of bres.…”
Section: Introductionmentioning
confidence: 99%
“…Copolymerization, blending with other polymers, and use of additives have been explored to modify the properties of PBT. [19] Fundamental features of PBT/epoxy blends, such as crystallization kinetics, [20,21] and rheological behavior, [22][23][24] have been widely investigated.…”
Section: Introductionmentioning
confidence: 99%